Comparison of financial distress between manufacturing companies in the ceramic, porcelain, and glass sector with agriculture sector - Edy Suprianto; Lifza Priyangga Putra; Ahmad salim (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Rapid technological development, high economic growth rates and the development of complex demands have resulted in the emergence of various industries that only answer the needs of society. The purpose of the study is to determine the influence of independent variables, namely Liquidity, Activity and Leverage, on Dependent variables, namely Financial Distress of Agricultural Sector Companies and Ceramics, Glass and Porcelain Subsector Companies in 2017-2020 and compare the level of Financial Distress between Agricultural Sector Companies and Ceramics, Glass and Porcelain Subsector Companies using the Altman Z-Score method. The population to be studied in this study is all Agricultural Sector Companies and Ceramics, Glass and Porcelain Subsector Companies listed on the Indonesia Stock Exchange in 2017-2020. The sampling technique was selected using the purposive sampling method, obtaining observation data of 100 data. The analysis technique used in this study is multiple linear regression. Coefiseien determination, F test and t-test as measuring instruments were used. The study results showed that Liquidity does not affect Financial Distress, Activity, and Leverage affect Financial Distress, and the level of Financial Distress of Ceramics, Glass and Porcelain Subsector Companies is better than Agricultural Sector Companies.Profitability is important to measure a company's ability to generate profits. In this study, the level of profitability of each company during 2017-2020 varies; some companies experienced an increase in profit and a decrease in profit, this will certainly affect the results of research on the independent variable profitability.